Tatak Pilipino [episode no. 45] ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
Code of Kalantiaw (5 min.) -- Juan Luna's spolarium painting (5 min.) -- Body language (5 min.) -- Camiguin (2 min.) --Oldest Filipinos (10 min.) -- Isang tanong, isang sagot (3 min.) -- Silya electrika (10 min.) -- Anting-anting (10 min.) -- Potografia ni Masferre (5 min.) -- Historical rap calendar events of October (5 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Luna, Juan; Masferre -- Photograph collections; Kalantiaw, Code of .; Aged -- Philippines; Amulets -- Philippines; Capital punishment -- Philippines; Electrocution; Nonverbal communication (Psychology).; Philippines -- History; Psychology; Fine arts; Sociology; Laws